Ruwat Murwakala ritual: transmission of educational value through the traditional performing arts and its relevance with the implementation of the concept of merdeka belajar - Lardianto Budhi; Slamet Subiyantoro; Adam Wahida (International Journal of Visual and Performing Arts, 2022)
Besides being an expression of culture, traditional artworks carry various kinds of knowledge and values that are useful for the survival of the community. This is one of the reasons why a product of traditional artworks survives in the midst of the progress of the times. This research on the ruwatan murwakala ritual aims to; (1) find out how the transmission of educational values occurs in wayang performances; (2) Analyse the scenes in Ruwat Murwakala's story that show the process of transmitting educational values and supporting the implementation of the Merdeka Belajar idea. The method used in this research is descriptive qualitative interpretive. Data was collected through participant observation (observation), literature review and in-depth interviews. Observations were made by observing the performance directly or by looking at the recording of the performance of Ruwatan's play Murwakala. The study of library sources consisting of articles and writings related to the research subject aims to complete the research data. Triangulation of data sources and sources is used to validate the data obtained so that the validity of the data can be accounted for. The results of the research on the Ruwatan ritual of the Murwakala play show that there are findings in the form of a process of delivering character education values to the community, including curiosity; honesty and knight; respect; religion; obeying the rules; respect; fair; smart; creative; critical knights; honest; respectful; and intelligent. These values are contained in each chapter in the story of Ruwatan Murwakala, namely: the pathet nem scene (beginning), the pathet sanga scene (middle) and the pathet manyura scene (end)